2004
DOI: 10.1021/la0359676
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of Perfluoroalkyl Silane Self-Assembled on a Polycrystalline Aluminum Surface

Abstract: Thermal stability behavior of 1H, 1H,2H,2H-perfluorooctyl trichlorosilane self-assembled on aluminum substrates is characterized using a grazing-angle Fourier transform infrared spectrometer, Fourier transform-Raman spectroscopy, and contact angle measurements. The self-assembled monolayer (SAM) is heated quasi-statically from room temperature to above 633 K with a heating rate of 1 K/s. Variations in peak frequencies, integrated areas of intensities of symmetric and antisymmetric CF2 stretches, and the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 29 publications
3
52
0
1
Order By: Relevance
“…The significantly higher stiffness of the fluorocarbon molecules than that of the hydrogenated molecules have been demonstrated by a number of authors [49][50][51]. In a previous paper [20] we have attributed the high stiffness of fluroalkyls to its helical structure. Shear coordination does not necessary mean an overall decrease in friction as we observe by comparing the structural energy factor (-s/ ?…”
Section: Ordered Fots and Odts Monolayersmentioning
confidence: 75%
See 2 more Smart Citations
“…The significantly higher stiffness of the fluorocarbon molecules than that of the hydrogenated molecules have been demonstrated by a number of authors [49][50][51]. In a previous paper [20] we have attributed the high stiffness of fluroalkyls to its helical structure. Shear coordination does not necessary mean an overall decrease in friction as we observe by comparing the structural energy factor (-s/ ?…”
Section: Ordered Fots and Odts Monolayersmentioning
confidence: 75%
“…To check the polymerization of the FOTS SAM, we had [20] compared the IR spectra with those obtained for the molecules assembled from the gas phase. Close identity of the two spectra indicates that the FOTS monolayer assembled here is well packed with minimal lateral polymerization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SAMs of OTS are stable in air up to about 150 8C, [17,[77][78][79][80] after which irreversible changes occur in the monolayer structure. Perfluorinated SAMs appear to be even more resistant towards thermal decomposition: [78,81] Srinivasan et al reported that 1H,1H,2H,2H-perfluorodecyltrichlorosilane coatings remain intact even up to 400 8C. [78] The stability toward various chemicals is also remarkable: OTS SAMs can be washed with organic solvents, hot (tap) water, or detergent solutions without detectable damage to the layer.…”
Section: Stability Of the Self-assembled Monolayersmentioning
confidence: 99%
“…An der Luft sind SAMs von OTS bis zu einer Temperatur von 150 8C stabil, [17,[77][78][79][80] und erst bei Temperaturen darüber verändert sich die Struktur der Monoschicht irreversibel. Perfluorierte SAMs scheinen sogar noch beständiger gegen thermische Zersetzung zu sein: [78,81] Srinivasan et al berichteten von 1H,1H,2H,2H-Perfluordecyltrichlorsilan-Beschichtungen, die sogar bis 400 8C intakt bleiben. [78] Auch die Stabilität gegen verschiedene Chemikalien ist beachtlich -so können OTS-SAMs mit organischen Lösungsmitteln, heißem (Leitungs-)Wasser oder Reinigungslösungen gewaschen werden, ohne dass die Schicht dabei beschädigt wird.…”
Section: Stabilität Selbstorganisierter Monoschichtenunclassified